2014
DOI: 10.1111/mmi.12677
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei histone H1 inhibits RNA polymerase I transcription and is important for parasite fitness in vivo

Abstract: Trypanosoma brucei is a unicellular parasite that causes sleeping sickness in humans. Most of its transcription is constitutive and driven by RNA polymerase II. RNA polymerase I (Pol I) transcribes not only ribosomal RNA genes, but also protein-encoding genes, including variant surface glycoproteins (VSGs) and procyclins. In T. brucei, histone H1 (H1) is required for VSG silencing and chromatin condensation. However, whether H1 has a genome-wide role in transcription is unknown. Here, using RNA sequencing we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 74 publications
(118 reference statements)
1
35
1
Order By: Relevance
“…Similar de-repression of a promoter-proximal reporter gene was observed when the histone deacetylase DAC3 (Wang et al, 2010), the linker histone H1 (Povelones et al, 2012; Pena et al, 2014), or the nucleoplasmin-like protein NLP (Narayanan et al, 2011) was depleted. The function of DAC3 appears to be promoter-specific since expression of the VSG gene in the marked BES was unaffected at both the mRNA and the protein level (Wang et al, 2010).…”
Section: Factors Involved In Bes Transcription Regulationmentioning
confidence: 61%
See 1 more Smart Citation
“…Similar de-repression of a promoter-proximal reporter gene was observed when the histone deacetylase DAC3 (Wang et al, 2010), the linker histone H1 (Povelones et al, 2012; Pena et al, 2014), or the nucleoplasmin-like protein NLP (Narayanan et al, 2011) was depleted. The function of DAC3 appears to be promoter-specific since expression of the VSG gene in the marked BES was unaffected at both the mRNA and the protein level (Wang et al, 2010).…”
Section: Factors Involved In Bes Transcription Regulationmentioning
confidence: 61%
“…Histone H1 is important for chromatin architecture and generally functions in chromatin condensation and transcription repression (Happel and Doenecke, 2009). Accordingly, co-silencing of the T. brucei H1 multigene family opened up chromatin globally with the strongest effect on silent BES promoters (Pena et al, 2014). Metabolic labeling of nascent RNA then showed that histone H1 depletion resulted in an approximately six-fold higher promoter-proximal transcription rate at a silent BES, indicating that relaxation of the nucleosome structure in the promoter region led to an increase of the transcription initiation rate at the silent BES (Pena et al, 2014).…”
Section: Factors Involved In Bes Transcription Regulationmentioning
confidence: 99%
“…In addition, a broad range of chromatin proteins, remodellers and histone chaperones have now been shown to be involved in ES control. Knockdown of chromatin proteins and remodellers (ISWI, NLP, RAP1), histone chaperones (FACT, ASF1, CAF-1b), histone modifiers (DAC3, DOT1B), or histones H1 or H3 results in derepression of silent ES promoters or changes in VSG switching (Hughes et al ., 2007 ; Figueiredo et al ., 2008 ; Yang et al ., 2009 ; Denninger et al ., 2010 ; Wang et al ., 2010 ; Narayanan et al ., 2011 ; Alsford and Horn, 2012 ; Povelones et al ., 2012 ; Pena et al ., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Formaldehyde-assisted isolation of regulatory elements (FAIRE) was performed essentially as described previously (Pena et al 2014). In brief, a total of 1.2 9 10 8 cells were fixed for 10 min in 1% PFA in PBS.…”
Section: Faire Techniquementioning
confidence: 99%